Social benefits in urban China: Determinants and impact on income inequality in 1988 and 2002 - Qin Gao (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
This study provides the first set of empirical evidence on the determinants of social benefits received by urban families in China and the impact on income inequality using the China Household Income Project (CHIP) 1988 and 2002 data. It finds that the total urban social benefits strongly targeted the bottom pre-tax pre-transfer income decile. Cash transfers were negatively associated with income distribution in both years, while important in-kind benefits (namely health and food in 1988 and education in 2002) were positively related to income levels. The presence of elder members and higher education levels were significantly related to more total social benefits. Urban social benefits played a significant role in reducing income inequality in both 1988 and 2002. However, the social benefit transfers were not able to close the increasing income gap caused by the growing market income inequality of the period. As a result, post-tax post-transfer income inequality level in 2002 was higher still than in 1988.
Keywords: H23; I38; R13; 330; social benefits; China; urban income inequality; Sozialhilfe; Einkommensverteilung; Stadtbevölkerung; China